Dari Solusi kepada Delusi: Kajian Biblika Kisah Tiang Ular Tembaga Dalam Bilangan 21:4-9 dan 2 Raja-raja 18:4 - Pattinaja, Aska Aprilano; Priyono, Joko (Student Evangelical Journal Aiming At Theological Interpretation, 2025)
This research aims to explore the changing meaning of the copper snake from a symbol of salvific solution to a delusional object of idolatry. There is a gap in research because it was found that some previous studies only discussed historical, mythological, and cultural aspects without exploring the theological and implicative depth of the text. Based on the biblical hermeneutic method, this study produces three important findings: (1) God-given symbols of salvation can turn into idols if they lose their theological meaning; (2) True faith must be directed to God, not to religious means or traditions; (3) Spiritual reformation requires Hezekiah-like courage to destroy deviations for the sake of purifying faith. This study focuses on the relationship between faith and worship of the Israelites, and its relevance to the lives of believers today who often turn from true worship to modern forms of idols.